Emergence of wet conditions in the Mono Basin of the western USA coincident with inception of the Last Glaciation - Ali, Guleed Ahmed Hussein (2022)
At present, the Basin and Range of the western USA is arid, but geologic studies show evidence of past wetness. The timing of these wetter conditions reveals a close association with glacial conditions. This association has led to the hypothesis of a causal link between glacial climate and regional wetness, but poor age control on the onset of regional wetness thwarts a test of this hypothesis. Here we determine the start of the most recent interval of persistent wetness in the Mono Basin, which is a hydrologically closed depression that sits at the west-central edge of the Basin and Range. The most recent emergence of persistent wetness in the Mono Basin is stratigraphically correlated with the depositional age of Ash 19—a rhyolitic ash bed that represents the oldest tephra of the Wilson Creek Formation and one of the earliest-known products of explosive volcanic activity from the Mono Craters. We constrain the depositional age of Ash 19 by using the U/Th disequilibrium dating method to date carbonates that are younger and older than Ash 19. Our U/Th dating results show that Ash 19 was deposited before the formation of a cross-cutting carbonate bed dated to 69.2 ± 0.3 ka but after an underlying carbonate tufa dated to 67.4 ± 3.5 ka, which suggests that the start of wetness in the Mono Basin was contemporary with the inception of the Last Glaciation—the beginning of Marine Isotope Stage 4—at ca. 70 ka. This finding corroborates the hypothesis of a link between glacial climate and regional wetness.